Insight into the effect of CeO2 morphology on catalytic performance for steam reforming of glycerol. (15th February 2023) - Wang, Yunzhu; Zhao, Yi; Zhu, Songshan; Lu, Jichang; He, Sufang; Lu, Huihui; Song, Di; Luo, Yongming
Graphical abstract: Highlights: Ni/CeO2 -S catalysts with the (1 1 1) planes as the main exposed crystalline surface exhibited an enhanced metal-support interaction. Regulatory mechanism of nickel-alumina interaction on active nickel and oxygen vacancies was elaborated. Ni/CeO2 -S with strong nickel-alumina interaction achieves a high catalytic activity and long-term stability (>25 h). Activated nickel and oxygen vacancy dual-active interface sites enhanced catalytic performance. Abstract: Shape-specific CeO2 nanocrystals (spheres, rods, cubes and nanoparticles) with well-defined crystal facets were successfully synthesized and used as the support to synthesize series Ni/CeO2 . Ni/CeO2 was employed as the model catalysts to study the structure dependent behavior and reaction mechanism for hydrogen production from glycerol steam reforming (GSR). The metal-support interaction was finely tuned by altering the morphology of CeO2 support, which in turn affected the exposed specific surface area of nickel and oxygen vacancy concentration. The relationship between exposed surface area of active nickel as well as surface oxygen vacancies and catalytic performance was studied. Ni/CeO2 -S with the mainly exposed (1 1 1) type planes obtained the strongest metal-support interaction. Electron effects due to the strong metal-support between nickel and cerium dioxide facilitated the formation of readily reducible nickel species (Ni δ+ ). High nickel reduction and nickel dispersion contributed to the maximum active nickel exposure surface area, thus Ni/CeO2 -S showed exceptional glycerol conversion. Meanwhile, the strong Ni-CeO2 interaction resulting in abundant oxygen vacancies that facilitated the dissociation of water to produce hydrogen, thus possessing a high H2 yield. Conversely, Ni/CeO2 -NR and Ni/CeO2 -NC have lower exposure areas and oxygen vacancy concentrations due to the different exposed crystal planes, and therefore have relatively poor catalytic activity. Moreover, the strong oxygen storage-release ability (CO-OSC-OSCC) promoted the oxidation of carbon deposition on Ni/CeO2 -S. Additionally, carbon deposition was mainly the filamentous carbon growing towards the periphery, hence, Ni/CeO2 -S obtained up to 25-h catalytic stability. The study of the regulatory role of Ni-CeO2 interaction on catalytic behavior can offer worthwhile direction for designing high-efficiency GSR catalysts.